Dynamics of microbial community and fermentation quality during ensiling of sterile and nonsterile alfalfa with or without Lactobacillus plantarum inoculant. (March 2019) - Yang, Lili; Yuan, Xianjun; Li, Junfeng; Dong, Zhihao; Shao, Tao
Highlights: γ-Ray irradiation was used to exclude the effect of epiphytic microorganisms. Pediococcus was the dominant microorganism in alfalfa silage. Inoculation of L. plantarum increased the relative abundance of Lactobacillus. Irradiated alfalfa with L. plantarum showed best fermentation quality. Abstract: To reveal the mechanism of the survival and adaption of inoculated Lactobacillus plantarum during ensiling. Alfalfa was ensiled directly (A1), after γ-ray irradiation (A0), and after inoculation of the sterile (A0L) or fresh alfalfa (A1L) with Lactobacillus plantarum . The A0L had the higher lactic acid content and lower pH than that in A1L from 3 days of ensiling. Pediococcus was the dominant microbes in A1 silage, followed by Enterococcus and Lactobacillus, while Lactobacillus in A1L outnumbered all other genera at 3 d. In A0L silage, the relative abundance of Lactobacillus increased to 99.13% at day 3. It indicated that Lactobacillus could dominated the fermentation of inoculated silages regardless of the γ-ray irradiation, although there was a short lag period for irradiated alfalfa.